Effect of Trichoderma reesei Degraded Date Pits on Antioxidant Enzyme Activities and Biochemical Responses of Broiler Chickens - Alyileili, Salem R.; El-Tarabily, Khaled A.; Belal, Ibrahim E. H.; Ibrahim, Wissam H.; Sulaiman, Mohsin; Hussein, Ahmed S. (Frontiers in Veterinary Science, 2020)
The long-term use of antimicrobials as growth promoters in poultry feed leads to antimicrobial resistance in pathogens. Thus, alternatives to antibiotics are essential for reasons associated with both safety and cost-effectiveness. Underutilized plant sources need to be developed to replace antibiotics in broiler feed. Several feed resources have been introduced so far, but they have yet to be applied widely. Date pits are a major by-product of the date industry (6–8%) of dates and have the potential to replace antibiotics. In this study, fresh date pits were degraded using the fungus Trichoderma reesei under solid-state degradation (SSD), resulting in degraded date pits (DDP). A total of 180 Brazilian “Cobb 500” broiler chicks were divided into six feed treatments in triplicate groups. The treatments were corn-soy basal diet (positive control; C+), corn-soy + 20% oxytetracycline at 0.05% (negative control; C-), corn-soy + 10% DDP, corn-soy + 0.2% mannan oligosaccharides (MOS), corn-soy + 0.1% mannose, and corn-soy + 0.2% mannose. The antioxidant and biochemical effects of DDP, MOS, and mannose were determined in the blood serum, liver, and intestine of broilers at age 21 and 42 days. The results indicated that the contents of antioxidants such as flavonoids and phenolics, as well as the MOS content in DDP, were increased by the degradation process. Additionally, mannose, glucose, arabinose, rhamnose, and glucuronic acid were significantly increased in DDP after degradation. The activity of antioxidant enzymes (GPX – glutathione peroxidase, catalase, and SOD – superoxide dismutase) in the serum, liver, and intestine of broilers fed diets containing 10% DDP and 0.2% MOS was increased significantly compared to the control group. Malondialdehyde activity was decreased whereas the mean corpuscular hemoglobin level and the iron content were significantly upregulated in the broilers fed the 10% DDP, 0.1% mannose, and 0.2% MOS diets compared with the control. Thus, DDP can be used to improve the antioxidant status and has a prebiotic effect in broiler chickens.